The Political Conditions in Deir ez-Zor ‎‎(December 7, 1918 - January 11, ‎‎1919)‎ - Yasmin Mohammed Mahmoud; Yousif Sami Farhan (مجلة جامعة الأنبار للعلوم الإنسانية)
Aims: This study aims to investigate the political and administrative circumstances in Deir ez-Zor after the Ottoman withdrawal in 1918. It also analyzes the experience of the provisional government formed by the residents and the role of prominent figures in managing the transitional period. It also highlights the reasons for the residents' shift from supporting the Arab government in Damascus to seeking British intervention. Methodology: The research adopted the historical and analytical approach to study the political events after the Ottoman withdrawal. The researcher also analyzed the historical documents and references using a descriptive approach to trace the follow up the evolution of the situation within the city and the impact of political transformations on its residents. Results: After analyzing all the data, the results showed that the Ottoman withdrawal led to a political chaos which prompted the locals to form a temporary local government headed by Fadel al-Aboud, known as the "government of lawlessness". Despite the local government's attempts to restore law, it was unable to address the administrative and economic challenges which enforced the government to request to join the Arab government in Damascus, which sent Mar'i Pasha al-Mallah to be the mayor of the city. Conditions quickly deteriorated under the new administration, leading to discontent among the population and a loss of confidence in the Arab government. As propaganda about the improvement in conditions in Iraq under British rule mounted, the notables of Deir ez-Zor began to view the British as a more acceptable solution, prompting them to invite the British into the city. Conclusions: It can be concluded that the period followed the Ottoman withdrawal was turbulent, as local and Arab governments failed to achieve stability, leading residents to seek British protection. The study recommends studying the long-term effects of this shift on Deir ez-Zor and the extent to which British policies fared compared to those of the Arab government.